Личинка и куколка слепня Tabanus airopathenicus (Diptera, Tabanidae) и место этого вида в системе рода Tabanus - Долин, В.Г.; Андреева, Р.В. (Вестник зоологии, 1984)
Larva and Pupa of Tabanus atropathenicus (Diptera, Tabanidae) and Position of This Species Within Genus Tabanus. Dolin V. G, Andreev R. V.— Vesin. zool, 1984, No 1. Formerly unknown larva of Tabanus atropathenicus differs from all representatives of the genus by some essential characters.-A complex study of larval and imaginal characters suggests an outstanding position of the species within Tabanus, not within a 7. autumnalis